(untitled) (Revista Contexto & Saúde, 2025)
Objective: To identify nurses’ understanding of the barriers and strategies for promoting health literacy among the elderly in primary health care. Method: A qualitative research of the descriptive exploratory type was carried out with 12 nurses linked to health units in the city of Arapiraca/AL. Data exploration occurred by thematic analysis of Minayo. Results: Four thematic categories related to understanding, skills, barriers and strategies for developing literacy in the health of the elderly emerged. The main barriers were lack of training, time of attendance, limitations related to aging, internet access and schooling. The strategies included use of simple language, teach-back method and use of visual resources. Conclusion: The nurses identified strategies to help the elderly and recognized the barriers that hinder the promotion of health literacy. Future interventions should focus on developing literacy skills in elderly health.